The Dopan Influence to Electrical Properties of Nanofibre Polyaniline Synthesize by Interfacial Polymerization - Ngurah Ayu Ketut Umiati; Nurlaila Rajabiah; Kuwat Triyana; Kamsul Abraha (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
The study observed the effect of variations in the electrical properties of dopants molarity polyaniline nanofiber. Polyaniline nanofiber in this study is synthesized by the interfacial polymerization method in Toluene Aniline 0.31 with the APS 4mmol dopant HCl solution with molarity between 0.6 M to 2.4 M. The synthesis results obtained were characterized by Scanning Electron Microscope. The electrical property is also observed on the polyaniline nanofiber. The results of this study indicate that the increase in molarity of dopants affect the incremental conductivity and diameter of fiber of the material.